Desenvolvimento moral e trapaça: um estudo com crianças e adolescentes - Pessotti, Alice Melo (2015)
The human interest about the morality is not a new phenomenon, as discussions on this subject date back to ancient times, such as the reflections of Aristotle (384-322 BC / 1992). This research investigates the relationship between the level of moral development and cheating in children and adolescents using game of rules, based on Piaget's theory. 60 children and adolescents aged 5, 10 and 15 years of age from private schools on primary and secondary education levels in the city of Linhares / ES have participated in this study.For data collection it was used: (a) the Evaluation Instrument of Moral Development Level (EIMDL), (b) the traditional version of the board game guess who with children 5 to 10 years of age and another version of the game tailored for teenagers called “Noah's Ark”, and (c) Post-Game Interview script. The obtained data was analyzed in quantitative and qualitative terms, as the guidelines of Delval (2002) for surveys were conducted from clinical method. It was elaborated a criteria for assessing the Moral Development Level (MDL) and cheating, called analysis criteria of Cheating level (CL). The levels include the Level I, Level II and Level III. The results has shown an evolution in the participants moral development level, mainly to the 5 years old on Level I, at age 10, Level II and at age 15 Level II and III. Concerning the action of cheating, this behavior also tends to decrease with age, as most of the participants of age 5 cheat, whereas by those at age 10 such behavior is less frequent, and among those at age 15, there was no cheating. Regarding the judgment of the action itself, the minority of participants who cheated confessed the crime. The results of trickery level indicated that most children at age 5 have remained at Level I, while the 10-year-olders were divided on all other levels, and among adolescents, again it has happened a predominance of the highest levels.Regarding the level of moral development and the cheating level there were mainly a correspondence of the two levels in the participants of age 5 and 10 years old and a better result in the cheating level relative to the level of moral development in participants of age 15. The higher the age is it becomes clear that the action is more developed than moral thinking, as noted by Piaget (1932/1994). Based on this finding, it is undeniable the importance of intervention through educative projects in moral values to promote reflections on issues and moral behavior in order to stimulate the construction of autonomous and ethical values.